Effects of Neem (Azadirachta indic) and Custard Apple (Annona reticulata) Diets on Sterility of House Rat (Rattus rattus) - Sharma, Prem Nidhi; Shrestha, Poorna Dass Dhaubaji; Chauhan, Shiv Raj; Sharma, Vinita (Journal of Nepal Agricultural Research Council, 2016)
Three different plant products diets – i) neem (Azadirachta indic A. Juss) oil mixed diet (neem oil mixed @ 80 ml/kg of normal diet), ii) neem seed powder mixed diet (neem seed powder mixed @ 80 g/kg of normal diet) and iii) custard apple (Annona reticulata L.) seed powder mixed diet (custard apple seed powder mixed @ 80 g/kg of normal diet) were separately fed to mature rats (Rattus rattus) with single dose feeding of 80 g per pair in a day on 13th week-age during the experimenting years, 2012/013 and 2013/014. In control group only normal diet without neem and custard apple constituents were fed. Sterility test of rat was conducted up to 38 and 28 weeks-age in first and second year, respectively. The test rats were fed normal diet during whole experimenting periods except the one day when they were fed only the neem or custard apple mixed diet on the age of 13th week. Efficacy of the mixed diets on rat-sterility was determined based on pregnancy and parturition by the rats. The two years' results confirmed that all the tested three mixed diets – neem oil mixed diet, neem seed powder mixed diet, and custard apple seed powder mixed diet were effective to stop pregnancy and parturition in rats during whole experimenting periods up to 38 and 28 weeks-age with single dose feeding of 80 g per pair (40 gm/rat) in a day on 13th week-age of the rats; whereas the pregnancy and parturition were observed in the rats that were fed only the normal diet. It is expected, neem and custard apple mixed diets can be utilized in reducing the economically important rodent populations in rice-wheat cropping system in future. Journal of Nepal Agricultural Research Council Vol.1 2015, pp.37-40